The occurrence and management of postoperative pain in paediatric patients on discharge from the recovery room of the Charlotte Maxeke Johannesburg Academic Hospital - Hlatshwayo, Nozipho Philominah (My University, 2017)
Background Postoperative pain in children remains high despite an improvement in assessment and management. Assessment is done using developmentally appropriate tools including the Wong and Baker FACES® Scale (WBS). Management of immediate postoperative pain is done using intravenous or regional analgesic techniques. The aim of this study was to describe the occurrence and management of postoperative pain in paediatric patients on discharge from the recovery room of the Charlotte Maxeke Johannesburg Hospital operating theatres using the WBS. Methods A prospective, descriptive and contextual study was conducted over a three month period. Convenience sampling was used and 124 participants from various surgical disciplines aged 4 to 12 years were included in the study. Pain scores were assessed using the WBS in the recovery room immediately postoperatively. Results Of the 124 participants, 113 (91%) had adequate pain control. Fifteen percent (6/40) of general surgery and 9% (3/35) of orthopaedic patients that had pain 67% (4/6 and 2/3 respectively) had intravenous analgesia only whilst 33% ( 2/6 and 1/3 respectively) had a combination of intravenous and regional analgesic technique. One participant each from the ENT and ophthalmology groups had inadequate pain control and had received intravenous only analgesia. There was no statistically significant difference between those that had received intravenous only and combined intravenous and regional analgesic techniques (p= 0.199) or between males and females with regards to WBS score reported (p=0.511). Conclusion The assessment of pain scores in the recovery room show adequate pain control in the immediate postoperative period. A large percentage of those with inadequate pain control had undergone a general surgery or orthopaedic procedure. In addition a greater number of these participants had an intravenous only analgesic technique although the difference was not statistically different to those that had a combination of analgesic techniques.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in the fulfilment of the requirements for the degree of Masters of Medicine in the branch of Anaesthesiology. Johannesburg, 2016.
Keywords: Pain, Postoperative; Pediatrics